SPECIFIC FEATURES OF MANAGEMENT SCIENCE IN NURSING PRACTICE AND THE ESSENCE OF MANAGEMENT COMPETENCIES - Otashekhov Zokir Ismailovich; Shakirova Dildora Davlyatovna (Journal Park Publishing, 2025)
This article highlights the specific features of management science in nursing practice and reveals the essence of management competencies. In the healthcare system, the role of nurses is closely related not only to patient care but also to management activities. Therefore, studying management science in nursing, developing leadership skills, and improving professional competencies are of great importance. The article analyzes the main functions of nursing management, the distinctive aspects of the management process, and the key management competencies required for a modern nurse leader. The results of the study substantiate the significance of management knowledge in nursing practice for ensuring effective medical services.
Keywords: Nursing, management science, nursing management, management competencies, healthcare system, nurse manager.